PENDIDIKAN KARAKTER ISLAMI ANAK USIA DINI DI PAUD SEURAMOE JAYA - Ismail Darimi (AWLADY : Jurnal Pendidikan Anak, 2018)
Giving a good example as an Islamic character to a child is the starting point of a child introduced to have a good personality so that he can become a righteous child. The role and figure of an educator or a teacher is a milestone in the formation of akhlaqul karimah for students. The process of formation of early childhood morality, namely: First, through qudwah, uswah (exemplary) teacher; Second, through ta'lim (teaching); Third, ta'wid (habituation); Fourth, Targhib / reward, motivation (giving motivation); Fifth, Tarhib / punishment, warning (giving threats and legal sanctions).